2006
DOI: 10.1016/j.str.2005.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis of RNA Binding Discrimination between Bacteriophages Qβ and MS2

Abstract: Sequence-specific interactions between RNA stem-loops and coat protein (CP) subunits play vital roles in the life cycles of the RNA bacteriophages, e.g., by allowing translational repression of their replicase cistrons and tagging their own RNA genomes for encapsidation. The CPs of bacteriophages Qbeta and MS2 each discriminate in favor of their cognate translational operators, even in the presence of closely related operators from other phages in vivo. Discrete mutations within the MS2 CP have been shown to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 36 publications
1
34
0
Order By: Relevance
“…The complex has provided a wealth of structural data on the basis of the sequence-specific recognition events. 7,9,11 The TR sequence encompasses the start codon of the viral replicase, and CP dimer binding leads to translational repression of this cistron. Complex formation also results in an allosteric conformational change within the protein, taking it from a largely symmetric structure to an asymmetric one.…”
Section: Introductionmentioning
confidence: 99%
“…The complex has provided a wealth of structural data on the basis of the sequence-specific recognition events. 7,9,11 The TR sequence encompasses the start codon of the viral replicase, and CP dimer binding leads to translational repression of this cistron. Complex formation also results in an allosteric conformational change within the protein, taking it from a largely symmetric structure to an asymmetric one.…”
Section: Introductionmentioning
confidence: 99%
“…Biochemical experiments have shown that both coat proteins bind their own RNA hairpins with high affinity (K d ~ 1 nM) and are able to discriminately bind in favor of their own RNA by ~1,000-fold 3,4 . In contrast to the PP7 coat protein, the Qβ coat protein also shares low sequence identity (21%) with the MS2 coat protein, yet it uses an RNAbinding mode similar to that of the MS2 coat protein [5][6][7] Fig. 1 and Supplementary Methods online).…”
mentioning
confidence: 99%
“…3) strongly resembled each other. The ␤-sheets E, F, and G (RNA binding region) (10,13) and the interacting C-terminal helixes especially were conserved. The greatest differences were in the flexible loop regions.…”
mentioning
confidence: 99%